BDNF-triggered events in the rat hippocampus are required for both short- and long-term memory formation - Alonso, Mariana (2002)
Information storage in the brain is a temporally graded process involving different memory types or phases. It has been assumed for over a century that one or more short-term memory (STM) processes are involved in processing new information while long-term memory (LTM) is being formed. Because brain-derived neutrophic factor (BDNF) modulates both short-term synaptic function and activity-dependent synaptic plasticity in the adult hippocampus, we examined the role of BDNF in STM and LTM formation of a hippocampal-dependent one-trial fear-motivated learning task in rats. Using a competitive RT-PCR quantitation method, we found that inhibitory avoidance training is associated with a rapid and transient increase in BDNF mRNA expression in the hippocampus. Bilateral infusions of function-blocking anti-BDNF antibody into the CA, region of the dorsal hippocampus decreased extracellular signal-regulated kinase 2 (ERK2) activation and impaired STM retention scores. Inhibition of ERK1/2 activation by PD098059 produced similar effects. In contrast, intrahippocampal administration of recombinant human BDNF increased ERK1/2 activation and facilitated STM. The infusion of anti-BDNF antibody impaired LTM when given 15 min before or 1 and 4 hr after training, but not at 0 or 6 hr posttraining, indicating that two hippocampal BDNF-sensitive time windows are critical for LTM formation. At the same time points, PD098059 produced no LTM deficits. Thus, our results indicate that endogenous BDNF is required for both STM and LTM formation of an inhibitory avoidance learning. Additionally, they suggest that this requirement involves ERK1/2-dependent and -independent mechanisms.